Three new species of free-living nematodes from the South-East Atlantic Abyss (DIVA I Expedition) - Tchesunov, Alexei V. (Zootaxa, 2008)
Three new nematode species were found in the Angola Basin (south-east Atlantic Ocean) at depths of about 5500 m. Paracyatholaimus diva sp. nov. (Cyatholaimidae) is characterised by outer labial and cephalic setae of about 3–5 μm, multispiral amphidial fovea with six turns in males and four turns in females situated at the level of the dorsal tooth, buccal cavity armoured with only one prominent dorsal tooth, tail consisting of anterior conical and posterior slender cylindrical half portions, and six preanal midventral setose supplementary organs. Paracyatholaimus diva sp. nov. is most similar to Paracyatholaimus rotundus Gerlach, 1964 but differs by slightly longer body (936–1176 μm versus 705 μm), tail shape (with clearly narrowed posterior half versus conical), six versus four supplementary organs of different shape. The genus Paracyatholaimus Micoletzky, 1923 is briefly reviewed. The genus now includes twenty-four valid species. Five species are considered as species inquirendae, mainly because of inadequate type material lacking adult stages and/or incomplete descriptions. A pictorial guide for identification of the valid species of Paracyatholaimus is provided. Pomponema proximamphidum sp. nov. shares subapical position of the amphidial fovea and distinct lateral differentiation of the somatic cuticle with five Pomponema species: P. concinnum Wieser, 1954, P. corniculata Gourbault, 1980, P. mirabile Cobb, 1917, P. multipapillatum Filipjev, 1922 and P. stomachor Wieser, 1954 but differs from them by tail length, longer posterior cylindrical portion of the tail, relative width of the amphidial fovea, position of the ventral pore and lesser number of supplementary organs. Desmodora striatocephala sp. nov. is well characterized by a combination of very large amphidial fovea occupying nearly the entire lateral surface of the cephalic capsule and thickened midventral preanal cuticle with a few supplementary papillae inserted therein in males. D. striatocephala sp. nov. differs from related species D. cuddlesae Inglis, 1963 and to some lesser degree with D. inflexa Wieser, 1954 with shorter body, relative tail length, bigger size of the amphidial fovea and lesser number of supplementary papillae.